Intact navigation skills after bilateral loss of striate cortex. - de Gelder, B; Tamietto, M; van Boxtel, G; Goebel, R; Sahraie, A; van den Stock, J; Stienen, B; Weiskrantz, L; Pegna, A (2008)
A patient with bilateral damage to primary visual (striated) cortex has provided the opportunity to assess just what visual capacities are possible in the absence of geniculo-striate pathways. Patient TN suffered two strokes in succession, lesioning each visual cortex in turn and causing clinical blindness over his whole visual field. Functional and anatomical brain imaging assessments showed that TN completely lacks any functional visual cortex. We report here that, among other retained abilities, he can successfully navigate down the extent of a long corridor in which various barriers were placed. A video recording shows him skillfully avoiding and turning around the blockages. This demonstrates that extra-striate pathways in humans can sustain sophisticated visuo-spatial skills in the absence of perceptual awareness, akin to what has been previously reported in monkeys. It remains to be determined which of the several extra-striate pathways account for TN's intact navigation skills. © 2008 Elsevier Ltd. All rights reserved.